Scaling sets the limits of large scale membrane distillation modules for the treatment of high salinity feeds. (10th March 2021) - Soukane, Sofiane; Elcik, Harun; Alpatova, Alla; Orfi, Jamel; Ali, Emad; AlAnsary, Hany; Ghaffour, Noreddine
Abstract: In this study, the dynamics of scaled-up membrane distillation (MD) modules are tackled for the treatment of highly saline desalination brines. Physical phenomena occurring inside the feed chamber during process scale-up including temperature evolution, species distribution and scaling likeliness were explored using a multicomponent computational fluid dynamics (CFD) model that couples momentum, heat, ions transport and water permeation across the membrane. The model was calibrated with experiments carried out on a lab-scale direct contact MD system fed with concentrated seawater with a salinity of 61 g/L. The complete fall-off of the permeate flux occurred when the salinity reached 170 g/L from 61 g/L, caused by a scaling mostly due to calcium sulfate (gypsum). In order to predict scaling occurrence, an in-house code is embedded in the CFD model to solve Pitzer's equation at every cell of the domain, enabling the calculation of species activity coefficients, the feed ionic strength, species effective concentration and degree of saturation of the solution with respect to gypsum. Results unveil that during the MD process of brines, the degree of saturation increases considerably in membrane vicinity while the average outlet salinity remains close to that at the inlet due to the relatively high flow rate. Extrapolation to longer modules revealed that an increase in the feed temperature increases the scaling likeliness while flow rates, especially in the high range, did not significantly impact scaling formation. The drop in performance from lab-scale module to a scaled-up size is shown for 1 m long generic modules with and without the use of antiscalants. Highlights: Scaling is investigated with CFD during brine treatment in MD scaled-up modules. Experiments with concentrated seawater are carried out to validate the approach. Pitzer equations are solved in CFD code to get activities and degree of saturation. Scaling is shown to increase drastically with MD driving force. The outlet of large module exhibits the highest scaling proneness.